Expert consensus recommendations for managing hyperglycemia and rash in patients with PIK3CA-mutated, hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2–) advanced breast cancer (ABC) treated with alpelisib (ALP). Issue 28 (1st October 2022) - Gallagher, Emily J.; Moore, Heather; Lacouture, Mario E.; Dent, Susan Faye; Farooki, Azeez; Goncalves, Marcus D.; Isaacs, Claudine; Johnston, Abigail; Juric, Dejan; Quandt, Zoe; Spring, Laura; Berman, Brian; et al.
Abstract : 422 Background: ALP is a PI3Kα inhibitor and degrader approved with fulvestrant for the treatment (tx) of patients (pts) with PIK3CA -mutated, HR+, HER2– ABC. Hyperglycemia (HG) and rash are expected adverse events with ALP tx and remain a challenge for physicians and pts. Management guidance is primarily based on clinical trial experience, which is not necessarily reflective of real-world pts. Here we report guidance for optimizing prevention and management of HG and rash in pts taking ALP based on an integrated Delphi panel, a systematic, validated approach to organize consensus from experts in the absence of definitive evidence. Methods: Two modified Delphi panels were conducted, focusing on HG and rash, respectively. Each panel included 4 oncologists, 4 endocrinologists or dermatologists, 1 clinical pharmacist, and 1 pt advocate. Experts were asked to rate appropriateness of 908 interventions for HG and 348 for rash on hypothetical pt scenarios on a 1 (highly inappropriate) to 9 (highly appropriate) scale. Results were reviewed at virtual meetings, after which experts repeated the rating. The level of agreement or disagreement was determined using the median scores and dispersion from the final rating, and this level of agreement was used to develop consensus statements and tx algorithms. Results: Per the HG panel, (a) ALP tx is appropriate in individuals with HbA1c 6.5% to < 8% with a pre-tx endocrinology consult; (b) low carbohydrate diet is appropriate in all pts starting ALP; (c) prophylactic metformin is appropriate in pts with baseline HbA1c 5.7%-6.4%; may also be appropriate in pts with HbA1c < 5.7%; (d) after metformin, an SGLT2 inhibitor or a thiazolidinedione is an appropriate second-/third-line anti-HG agent (or first-line in metformin-intolerant pts), while insulin is not. Per the rash panel, (a) prophylactic nonsedating (NS) H1 antihistamines (standard dose) are appropriate for all pts; (b) starting/escalating NS H1 antihistamines and topical steroids (TS) is the preferred first step for managing rash; (c) it is appropriate to add, but not replace with, a sedating H1 antihistamine, if response to high-dose, NS option is inadequate, and to add an H2 antihistamine if response is still inadequate; (d) it is appropriate to hold ALP and start oral corticosteroids (OCS) if rash affects > 30% body surface area and is recurrent or has moderate/severe symptoms; (e) if angioedema is present, it is appropriate to either hold ALP and start OCS, or permanently discontinue ALP tx. Conclusions: Until further evidence is available, these expert recommendations provide guidance on prevention and management of HG and rash related to ALP tx in routine clinical practice.